Kemuning Leaves Extract Gel (Murraya panicula L.): A Study of Quality and Efficacy in Healing Burns - Hasbullah, Khairunnisa; Nonci, Faridha Yenny; Arsul, Muh. Ikhlas (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2020)
This study aims to determine the activity of kemuning leaves extract in healing burns, and efficacy and quality of the extract in gel dosage form. The research was started with kemuning leaves extraction used maceration method with ethanol 96%, ethyl acetate and n-hexane as solvent. Each extract was activity tested for healing burn in rabbits. The extract that is most effective in wound healing then formulated into gel. The gel preparations were made in 3 variations of concentration, namely 5% (FI), 10% (FII), and 15% (FIII), with basis by carbopol 940 gel, triethanolamine, and methyl paraben. Then, gels were tested for efficacy and quality. The efficacy test follows the activity test procedure. Gel quality test includes organoleptic, pH, viscosity, dispersibility, and homogenity. The activity test showed that ethanol 96% extract, ethyl acetate and n-hexane healed burns in 13,3; 14,3; and 15,3 days, respectively. While the results of the gel efficacy test for FI, FII and FIII were 13,6; 11,6; and 9,6 days, respectively. In general, all gels have good qualities in every parameter, except the viscosity of FII and FIII which is slightly higher. Based on the results of the research, ethanol 96% extract was the most effective in healing burn. In addition, FIII gel has the best efficacy with good qualities except viscosity.